NTQ volume 32 issue 2 Cover and Front matter (New theatre quarterly, 2016)
N volume xxxii . part 2 . may 2016 volume xxxii .part 2 .may 2016126 NEW THEATRE QUARTERLY 126 newtheatre quarterly POLITICAL THEATRE IN EUROPE SINCE 2007 WOMEN AT THE THEATRICAL DINNER TABLE AFTER THE YEARS OF LEAD IN MOROCCO PAST, PRESENT, AND THE POLITICS OF THE CRUCIBLE EXPLANATIONS AND IMPLICATIONS OF PSYSCHOPHYSICAL ACTING VIOLENCE ONSTAGE AND OFF IN AMERICAN DRAMA Subscriptions New Theatre Quarterly (issn: 0266-464x) is published quarterly by Cambridge University Press, University Printing House, Shaftesbury Road, Cambridge cb2 8bs, UK, and The Journals Department,32 Avenue of the Americas, New York, ny 10013-2473, USA. Organizations in the USA who are registered with C.C.C. may therefore copy material (beyond the limits permitted by Sections 107 and 108 of US copyright law) subject to payment to C.C.C. This consent does not extend to multiple copying for promotional or commercial purposes. Please see www.fsc.org for information. 2016 CAMBRIDGE UNIVERSITY PRESS University Printing House, Shaftesbury Road, Cambridge cb2 8bs, United Kingdom32 Avenue of the Americas, New York, ny 10013-2473, USA477 Williamstown Road, Port Melbourne, vic 3207, AustraliaC/Orense, 4, Planta 13, 28020 Madrid, SpainLower Ground Floor, Nautica Building, The Water Club, Beach Road, Granger Bay, 8005 Cape Town , South Africa Typeset by Country Setting, Kingsdown, Deal, Kent ct14 8es Printed in the United Kingdom by Bell & Bain Ltd, Glasgow NEW THEATRE QUARTERLY successor journal to theatre quarterly (19711981) volume xxxii part 2 may 2016 Editors Simon Trussler and Maria Shevtsova Assistant Editor Philippa Burt russell vandenbroucke 107 Violence Onstage and Off: Drama and Society in Recent American Plays changing modes of dramatizing violence, overt and covert, in recent work khalid amine 121 After the Years of Lead in Morocco: Performing the Memory testimony as performance and as therapy after an era of state oppression maria shevtsova 142 Political Theatre in Europe: East to West, 20072014 how can theatre be political in the face of neoliberal capitalist dominance? rose whyman 157 Explanations and Implications of Psychophysical Acting the Stanislavskian meaning and differing later approaches to the concept aamir aziz 169 Using the Past to Intervene in the Present: Spectacular Framing in Arthur Millers The Crucible the articulation of the writers experience of being judged unAmerican campion decent 181 The Ambiguous Table: Dramatic Representations of Women at Dinner how dramatists have related dining to the role and oppression of women 195 NTQ Book Reviews edited by Alison Jeffers 126 Published in February, May, August, and November by Cambridge University Press, University Printing House, Shaftesbury Road, Cambridge cb2 8bs, England issn 0266-464x Editors SIMON TRUSSLER Rose Bruford College MARIA SHEVTSOVA Goldsmiths, University of London Hon Advisory Editors Tracy Davis Declan Donnellan Brian Murphy Sarah Stanton Robert Wilson Contributing Editors Syed Jamil Ahmed University of Dhaka Eugenio Barba Odin Teatret Nicole Boireau University of Metz Mary Brewer De Montfort University Victoria Cooper Cambridge University Press Catherine Diamond Soochow University, Taiwan Oliver Double University of Kent at Canterbury Victor Emeljanow University of Newcastle, NSW Helga Finter University of Giessen Helen Freshwater Birkbeck, University of London Lizbeth Goodman University College Dublin Ian Herbert Founding Editor, Theatre Record Nadine Holdsworth University of Warwick Peter Holland University of Notre Dame Nesta Jones Rose Bruford College Kate E. Kelly Texas A&M University Dick McCaw Royal Holloway, University of London Bella Merlin University of California, Davis Peggy Paterson Former Director, script Dan Rebellato Royal Holloway, University of London Aleks Sierz Rose Bruford College Brian Singleton Trinity College, Dublin Nick de Somogyi Editor, The Shakespeare Folios Juliusz Tyszka Adam Mickiewicz University, Poznan Stephen Unwin Artistic Director, English Touring Theatre Ian Watson Rutgers University, Newark Rose Whyman University of Birmingham Don Wilmeth Brown University Editorial Enquiries Oldstairs, Kingsdown, Deal, Kent ct14 8es, England (simontrussler@btinternet.com) Unsolicited manuscripts are considered for publication in New Theatre Quarterly.